أهمية اظلنشطة البدنية والرياضية المنظمة في تعزيز الصحة النفسية ( النوم - القلق ) لدى منتسبي حديثا لجهاز الشطة لولاية مستغانم - بن شني, محمد (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
ملخص الدراسة هدفت دراستنا الموسومة ب "أهمية الأنشطة البدنية والرياضية المعدلة في تعزيز الصحة النفسية لدى منتسبي حديثا لجهاز الأمن الوطني (عينة أخذت لأمن ولاية مستغانم) إلى الكشف عن طبيعة النشاطات الرياضية والبدنية المعدلة الممارسة من طرف منتسبي الأمن الوطني وعن دورها في تعزيز بعض أبعاد الصحة النفسية لدى منتسبي الأمن الوطني حديثا المتمثلة في القلق والنوم، وقد اعتمدت الدراسة على المنهج الوصفي المقارن، كما تم اختيار عدد العينة المبحوثة ليكون عشرين (20) فرداً من المنتسبين للشرطة حديثا بولاية مستغانم، وقد استخدمت الدراسة مقياسين: مقياس القلق ومقياس اضطراب النوم، وأهم ما توصلت إليه الدراسة أن وجود دور هام لممارسة النشاطات البدنية والرياضية في تعزيز الصحة النفسية لمنتسبي الأمن الوطني الحديثين في ولاية مستغانم، حيث كانت مستويات القلق واضطرابات النوم أقل بشكل ملحوظ عند الممارسين للرياضة مقارنة بالأفراد الذين لا يمارسونها. Abstract: Our study, titled "The Importance of Organized Physical and Sports Activities in Enhancing Mental Health (Sleep and Anxiety) among Newly Recruited Police Officers in Mostaganem Province," aimed to explore the nature of sports and physical activities practiced by newly recruited members of the national security forces and their role in enhancing certain aspects of mental health, specifically anxiety and sleep. The study utilized a descriptive comparative methodology, selecting a sample of twenty (20) newly recruited police officers in Mostaganem Province. Two scales were used in the study: an anxiety scale and a sleep disorder scale. The most significant finding of the study was that engaging in physical and sports activities plays a crucial role in enhancing the mental health of newly recruited national security officers in Mostaganem Province. Anxiety levels and sleep disorders were notably lower among those who engaged in sports compared to those who did not.
MAPA-2024-3
Keywords: الأنشطة البدنية والرياضية المنظمة - الصحة النفسية ( النوم - القلق ) - جهاز الشرطة - مستغانم